A sustainability comparison of different traditional Chilean culinary preparations through an innovative method - Tiboni-Oschilewski, Ornella; Corvalán, Camila; Kanter, Rebecca (Frontiers in Sustainable Food Systems, 2025)
IntroductionDietary choices affect both human and planetary health; however, they are not always linked to public policies. For example, Food Based Dietary Guidelines (FBDGs) do not always consider sustainability in their recommendations. To date, no methods have been developed and agreed upon to assess the five sustainability dimensions proposed by the Food and Agriculture Organization (FAO) (nutritional, environmental, cultural, physical, and economical access) as a whole. The objective of this study was to compare the levels of sustainability of traditional Chilean culinary preparations using a newly proposed method that integrates five unique dimensions of sustainable diets with reference databases to generate recommendations about sustainable culinary preparations; in which the Chilean population serves as a test case.MethodsA database composed of 651 traditional Chilean culinary preparations was used. It was obtained through 10 focus groups from the Metropolitan Region. Culinary preparations were divided into eight different food groups based on their main ingredients. Sustainability estimations were conducted for physically accessible preparations. All the dimensions were estimated based on approaches and indicators previously used in scientific literature. Different weights were provided for all other dimensions: 30% for cultural and price, respectively, and 20% for nutritional and environmental dimensions. Culinary preparations we recommended as sustainable if they achieved a global sustainability score of 66% or above, provided each dimension individually scored 40% or above.ResultsAfter data management, 351 culinary preparations were analyzed. A total of 94 were selected as sustainable: 21/38 vegetables; 6/7 fruits; 28/105 proteins; 14/78 cereals; 6/41 soups; 0/32 dairy; 1/6 lipids; 18/443 beverages. The main reason a preparation was not classified as sustainable was failing to obtain 66% of global sustainability. No culinary preparations were excluded based on the economic dimension.DiscussionThis study shows that estimating sustainability of individual culinary preparations based on the five dimensions of sustainable diets of FAO is possible through the development of an innovative methodological approach that is useful for making dietary recommendations for a population, such as within FBDGs. Future research should continue developing this methodology as a tool for public health decision-making for healthier and sustainable diets. This would allow dietary patterns to develop into more sustainable ones, which is a useful strategy for public health and planetary health